Models of involvement of indigenous peoples in political decision making processes - Margarita V. Bukovska (Научно-аналитический вестник Института Европы РАН)
The article examines the experience of democratic countries in involving indigenous peoples in political decision-making processes. Since many indigenous peoples were subjected to discriminatory policies in the past, they had little chance to be heard. The article explores how countries and the global community have come to recognize the rights of indigenous peoples, including their political rights, and what models of inclusion of indigenous peoples in politics have become most popular in various democratic countries, specifically in Australia, New Zealand, Canada, Norway, Sweden, and Finland. The aim of the study is to examine the features of the models by which indigenous peoples are involved in political decision-making processes in democratic countries and to identify the factors influencing the choice of these models. The conclusion is that the most popular such models include the allocation of quotas in government bodies, creation of representative and consultative bodies, consultations with government agencies, as well as granting them territorial and non-territorial autonomy. It is emphasized that even in democratic countries, indigenous peoples still face difficulties in influencing politics and that the creation of special models is not always a guarantee of their full participation in political decision-making processes. One of the obstacles, in particular, is the persistence of discriminatory practices at some level towards indigenous peoples, which require resolution at the level of state policy.